2021
DOI: 10.3390/buildings11110499
|View full text |Cite
|
Sign up to set email alerts
|

Structural Fire Protection of Steel Structures in Arctic Conditions

Abstract: Most structures in the Arctic and Antarctic for oil and gas production are offshore stations, tankers, modules, steel supporting, and enclosing structures, which need to be protected against both cryogenic spills and fire exposure. Oil and gas industry facilities have products of high flammability and explosiveness, which in the case of ignition make it possible to develop a fire along the hydrocarbon curve, accompanied by a sharp jump in temperature and the formation of excessive pressure. This article discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Based on the analysis of scientific and technical literature [16][17][18][19], there are three ways of protecting steel structures against fire: the application of intumescent coatings, plaster compositions or the use of structural fire protection. Figure 1 shows a scheme of the means and methods of the fire protection of steel structures [20]. Structural fire protection is often used in harsh climates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the analysis of scientific and technical literature [16][17][18][19], there are three ways of protecting steel structures against fire: the application of intumescent coatings, plaster compositions or the use of structural fire protection. Figure 1 shows a scheme of the means and methods of the fire protection of steel structures [20]. Structural fire protection is often used in harsh climates.…”
Section: Introductionmentioning
confidence: 99%
“…In [22], it is shown that intumescent coatings are one of the effective means of passive fire Structural fire protection is often used in harsh climates. For example, in [20], tests of steel structures with structural fire protection on the example of super-thin basalt fibers in the Arctic region were demonstrated; the evaluation of various means of fire protection was carried out, the results of which showed that the most effective coatings for harsh Arctic conditions are materials containing super-thin basalt fibers. In [21], studies on structural fire protection used to increase the fire resistance limit of building structures used in oil and gas facilities are presented.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of an unprotected steel structure decreases significantly in the 400-600 • C range, and the structure loses stability almost immediately when loaded. In this regard, oil and gas facilities should use structures capable of withstanding high-temperature effects, i.e., protected by fire protection means [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are three main methods of fire protection of steel structures: intumescent coatings, plaster compositions or structural fire protection of structures [11][12][13]. Figure 1 presents a scheme of the means and methods of fire protection of steel structures [10]. Structural fire protection is often applied in harsh climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation